FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG KERACUNAN MAKANAN DI KECAMATAN ALUH-ALUH - Hijratun Wahana (LPPM Universitas Sari Mulia, 2020)
Background: Food poisoning is an emergency problem that causes death. Public knowledge in prehospital care is very important because knowledge is the spearhead in people's healthy behavior. Knowledge may be influenced by age, gender, education, occupation, information sources, and experience. Objective: To analyze factors related to the level of public knowledge about food poisoning in Aluh-Aluh District. Methods: Analytic correlation research design with a cross-sectional approach. The sample consisted of 100 respondents using cluster random sampling. The research instrument used a questionnaire which was analyzed univariately using a frequency distribution presented with a table and bivariate with the Pearson Chi-square test. Results: The factors of age, gender, education, work, and experience had no significant relationship with the level of knowledge with ρ value> 0.05) and there was a significant relationship between the source of information and the level of knowledge with ρ value = 0.000 (ρ value <0.05). Conclusion: Factors related to knowledge are sources of information.